2011
DOI: 10.1136/jfprhc-2011-100149
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of unscheduled re-attendance and contraception at discharge, among women having the final stage of early medical abortion at home and those remaining in hospital

Abstract: Introduction Throughout Great Britain, increasing numbers of women having an early medical abortion are choosing to go home soon after administration of misoprostol, to expel the pregnancy at home (early medical discharge, EMD), rather than remain upon the hospital premises (day case). However, data are lacking on how this impacts upon an abortion service in terms of unscheduled re-attendance rates and contraception provision at discharge. Methods A retrospective audit was carried out of women undergoing medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
(19 reference statements)
1
12
0
Order By: Relevance
“…Clearly the success of medical abortion is not dependent on the skill of the provider; however, one could hypothesise that if one setting provided superior advice or clinical expertise then that might impact upon the recognition of complications or the rate of intervention. The same low rate of women attending each site with a suspected complication (<3%) is reassuring and is no higher than previously reported among women after EMA 10. However, there was a higher telephone contact rate for the SRH setting.…”
Section: Discussionsupporting
confidence: 74%
“…Clearly the success of medical abortion is not dependent on the skill of the provider; however, one could hypothesise that if one setting provided superior advice or clinical expertise then that might impact upon the recognition of complications or the rate of intervention. The same low rate of women attending each site with a suspected complication (<3%) is reassuring and is no higher than previously reported among women after EMA 10. However, there was a higher telephone contact rate for the SRH setting.…”
Section: Discussionsupporting
confidence: 74%
“…If medical abortion is chosen, frequent non-compliance with the follow-up visit schedule can be expected. Studies have reported that 20-50% of women did not return for the follow-up visit [5,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Until October 2017, women in Scotland who wished to have an EMA were required to make an additional visit to the clinic to obtain misoprostol, the second of the drugs given for medical abortion. This was commonly self-administered by women in the clinic,5–7 after which they went home to abort the pregnancy. Women found these extra visits inconvenient and reported distressing bleeding or pain on their journey home due to the onset of action of misoprostol 8 9.…”
Section: Introductionmentioning
confidence: 99%